Reclamation of mine-impacted land for ecosystem recovery - Tripathi, Nimisha; Singh, Raj Shekhar, 1958-; Hills, Colin D. (John Wiley & Sons Inc., 2015)
"Reclamation of Mine-impacted Land for Ecosystem Recovery covers: methods of rejuvenation of mine wasteland including different practices of physical, chemical and ecological engineering methods"--